Environmental proteome profiling applied to the study of polybacterial metal resistance and adaptation - Lacerda, Carla M. R., author; Reardon, Kenneth F., advisor (Colorado State University. Libraries, 2008)
Environmental biotechnology can be defined as the use of biotechnology to solve environmental engineering problems, frequently involving bacterial communities and unsequenced species. Here we define environmental proteomics as the proteomic profiling of microorganisms of environmental relevance, targeting the improvement of environmental bioprocesses. This study demonstrates our ability to obtain proteomic data for communities of microorganisms and for environmental isolates, providing unique insights into the physiology and ecology of these systems. A combination of qualitative and quantitative proteomics methods (two-dimensional electrophoresis and/or chromatography followed by tandem mass spectrometry) was used to investigate the proteome of a sequenced mixed culture, an unsequenced mixed culture, and a bacterial isolate from the original unsequenced mixed culture. In the first case study, two soil organisms were grown in co-culture in an attempt to observe proteins induced as a response to the presence of another organism. Many proteome changes were detected and quantified, with proteins involved in protein and DNA metabolism being the most largely modulated. In the second case study, an unsequenced mixed culture was exposed to cadmium and had its dynamic response analyzed. While the community responded significantly to all shock durations, the greatest amount of change was observed in the first fifteen minutes of shock. The main groups of differentially expressed proteins identified were transport proteins, showing that the main method for cadmium tolerance was active efflux. In the study of the adaptation of a pure culture, the most cadmium-tolerant organism in the original unsequenced community was isolated and cultivated in different concentrations of cadmium. In the last case study of metal resistance, the proteomes of this isolate were compared as it responded to short-term exposures to chromium, iron and cadmium. Metals induced proteome responses in both short- and long-term exposures, meaning that the mechanisms for adaptation and resistance are different. This project demonstrates the potential of environmental proteomics and its intricacies as different proteomic workflows are employed. This is also one of the first evaluations of metaproteomic changes due to the metal response of mixed bacterial cultures, revealing the large potential of environmental proteomics to uncover unique insights into systems-level bacterial functions.
Keywords: bacterial; environmental; metal resistance; physiology; polybacterial; proteomics; chemical engineering